Editorial: Sexuality and Contraceptive Use (The East and Central African Journal of Pharmaceutical Sciences, 2018)
Sometimes in the early 1970s a sociology lecturer in the Institute of Developmental Studies (IDS), University of Nairobi attended an interview for the post of senior lecturer. The lecturer had several publications on the subject of sex and contraceptive use. He had been awarded a doctorate degree (Ph.D) in this field by an American University and subsequently obtained a research grant from an international agency. His research had gained international recognition. The appointment committee was chaired by the Vice-Chancellor. As is often the practice, the interview started on a light note. ‘Dr. X, I note that nearly all your publications are on the subject of sex; can you tell this committee how you developed an interest in this area?’ The candidate made a quick mental calculation at the same time noting that two of the committee members could barely suppress a mischievous smile. The candidate shot back, ‘if you do not like my publications, that is your problem not mine’. With that he picked up his documents and walked out in a huff. Soon after that the lecturer tendered his resignation and almost immediately got a job with an international Non-Governmental Organization (NGO). This incidence was widely discussed among academic staff. The exact words of the question posed by the Vice-Chancellor seemed to vary depending on the narrator.
Keywords: SEXUALITY AND CONTRACEPTIVE USE